BUSINESS COMMUNICATION CONNECTING AT WORK - MUKERJEE SANKAR HORY (NEW DELHI OXFORD UNIVERSITY PRESS, 2023)
Hory Sankar Mukerjee's "Business Communication: Connecting at Work" is a comprehensive textbook designed to equip postgraduate management students and professionals with the essential skills for effective communication in the corporate world. The book adopts a practical, practice-oriented approach, integrating theoretical concepts with real-world examples, case studies, and interactive features.
BUSINESS COMMUNICATION
BUSINESS COMMUNICATION
MBA & BBA
Keywords: BUSINESS COMMUNICATION; MANAGEMENT